EFEKTIVITAS PERATURAN PEMERINTAH NOMOR 56 TAHUN 2021 TENTANG PENGELOLAAN ROYALTI HAK CIPTA LAGU DAN/ MUSIK PADA KAFE DANTEMPAT KARAOKE ATAS PENGGUNAAN SECARA KOMERSIAL - Qotrunada, Alisa (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2023)
EFFECTIVENESS OF GOVERNMENT REGULATION NUMBER 56 OF 2021 CONCERNING ROYALTY MANAGEMENT OF SONG COPYRIGHTS AND/MUSIC ON THE CAFE AND KARAOKE PLACE COMMERCIAL USE (Research Study in Gianyar and Denpasar Regencies). Royalties are compensation or remuneration for the use of a work created by someone which includes copyrighted songs and/or music. Royalty payments collected by the National Collective Management Institute (LMKN) results will be given to creators, copyright holders and related rights owners as a form of permission or appreciation for the work that someone has created. This study aims to determine the Effectiveness of Government Regulation Number 56 of 2021 Concerning Management of Song and/Music Copyright Royalties that are used commercially in cafes and karaoke places in Gianyar and Denpasar Regencies and How are the efforts of the Provincial Government of Bali in supporting cafe and cafe business actors karaoke to carry out its obligations regarding the payment of song and/music copyright royalties. This study uses empirical research methods, namely data obtained directly from informants by conducting research in the field through observation, interviews and documentation related to research and practice. The results of the study concluded that Government Regulation Number 56 of 2021 concerning Management of Song and/Music Copyright Royalties is still not effective because in reality there are still many cafe and karaoke business actors in the Province of Bali, especially in Gianyar and Denpasar Regencies who do not carry out their obligations to pay royalties. There are various reasons for the reluctance of business actors not to pay royalties, one of which is because they have never known about the existence of regulations regarding these royalties. The government has now started to make several efforts so that the regulation regarding royalties runs as it should, one of which is conducting socialization but it has not run optimally.